Identification of specific antibodies against the Ag85C-MPT51-HspX fusion protein (CMX) for serological screening of tuberculosis in endemic area. (3rd August 2017) - Zagmignan, Adrielle; Costa, Adeliane Castro da; Viana, José Lima; Lima Neto, Lídio Gonçalves; Monteiro, Cristina de Andrade; Gaioso Neto, Ariosvaldo Guimarães; Junqueira-Kipnis, Ana Paula; de Sousa, Eduardo Martins
ABSTRACT: Objectives : Development of new tools for rapid and accurate diagnosis of tuberculosis (TB) is considered a strategy for controlling the disease. The recombinant CMX fusion protein is composed of immunodominant epitopes of the Ag85C (Rv0129c), MPT51 (Rv3803c) and the entire HspX (Rv2031c) proteins from Mycobacterium tuberculosis H37Rv (Mtb). The aim of this study was to evaluate the applicability of a test using the CMX protein in individuals suspected of TB. Methods : Indirect ELISA was used to measure serum anti-CMX IgM and IgG in individuals with pulmonary TB. Results : Patients with pulmonary TB had higher titers of IgM (OD = 0.502 ± 0.281) than healthy controls (OD = 0.200 ± 0.125). The cutoff for IgM-ELISA was determined using ROC curve analyzes (AUC = 0.868) with a sensitivity of 80.1% and a specificity of 78.2%. Patients with pulmonary TB also had higher titers of IgG (OD = 0.525 ± 0.391) than healthy controls (OD = 0.215 ± 0.077). The cutoff for IgG-ELISA was determined using ROC curve analyzes (AUC = 0.864) with a sensitivity of 81.7% and a specificity of 74.7%. Conclusion : The results suggest that the recombinant protein CMX can be used in a serological test to complement the screening of individuals suspected of having active pulmonary TB.